PERSEPSI SISWA TERHADAP PENGGUNAAN VIDEO DALAM PEMBELAJARAN BAHASA INGGRIS PADA MATERI SONG - Clementino Chiristobal Kopong Kolin; Rusijono Rusijono; Hari Sugiharto S. (Akademika : Jurnal Teknologi Pendidikan, 2023)
This study aimed to determine student perception after using English video learning media. The research method is a quantitative research method. The researcher uses pretest posttest control experiment to measure the effectiveness of Video Learning Media, before learning activity was held, the researcher determines students’ entry skill by giving them a pretest, furthermore the learning activity was held with the experiment class have a learning video as media and the control class not using a learning media. After that both classes took a posttest to find out the English skill enhancement which determine by using T-test. The result of t-test shows that experiment class obtained higher poin than control class which can be concluded that video learning media is more effective than not using video learning media at all. After the posttest the researcher collected data through questionnaire which given to 30 student of experiment Class XI Social 5 at SMA Negeri 1 Larantuka. After calculated the acquisition value of the questionnaire, the researcher obtained an average value of perception questionnaire (93) and also obtained the majority of each questionnaire item has a positive respond from the student. This shows that the using of English video learning media obtained a very good perception by the student in the classroom which directly proportional with higher posttest result achieved by experiment class. This finding can be considered as reference for the next studies about a relation between motivation, learning outcomes and the using of English Video learning Media